The Effect Of Crop Spacing And Dossage Of Potassium Fertilizer On Growth And Yield Of Sweet Corn (Zea mays Var. saccharata Sturt) Bonanza Cultivar - Nurliawati, Gita; Faqih, Achmad (Devotion : Journal of Research and Community Service, 2024)
The development of sweet corn in Indonesia using cultivation techniques in the form of crop spacing is expected to affect the plant population and affect the competition between plants in using water and nutrients, and the application of potassium fertilizer functions in the formation of sugar and starch, sugar translocation, enzyme activity and stomatal movement. The research was conducted in Gombang Village, Plered District, Cirebon Regency from March to June 2023. The treatment used a Randomized Group Design (RAK) factorial pattern consisting of two factors, namely crop spacing and potassium fertilizer dose, obtained 9 treatment combinations and repeated 3 times, so that in total there were 27 experimental plots. The results showed that the spacing of 50 cm x 40 cm (J2) and potassium fertilizer dossage of 100 kg K2O/ha (K2) showed the best effect on the weight of the corn cob with husks per plot which produced 31.85 kg/plot or equivalent to 21.23 tons/ha. There was a significant correlation between the growth components of plant height at 5 weeks and 6 weeks and the number of leaves at 4 weeks and 5 weeks with the weight of the corn cob with husks per plot.